Diversity and practice: local decision-making practices on multi-cultural diets for British Muslim school children (BMSC) and implications for social justice - Sattar, Zeibeda; Carr, Susan M.; Lochhead, Lydia; Defeyter, Margaret Anne (Frontiers in Public Health, 2024)
Introduction British Muslim School Children (BMSC) are required to follow special halal dietary requirements in accordance with their religion, which is often not accounted for in British schools. This often leaves BMSC limited to a vegetarian diet while at school, despite this not being their chosen diet or preference. This study explores the perceptions of key stakeholders regarding fairness and accessibility of school meals for BMSC, as well as discussing school food provision for those maintaining a religious diet in light of social justice. This is in the context of limited knowledge previously being explored in the North East of England regarding procurement and decision-making at a systems level to cater for BMSC. Methods A qualitative research design was conducted. A total of 62 participants (39 BMSC, 15 parents, and 8 school and catering staff) took part in a semi-structured interview or focus group. Participants were recruited from six schools, with these schools selected based on their differing levels of BMSC in attendance. This project took place between March 2022 and October 2023. Results/discussion Results suggested that where schools already catered for diverse food requirements, inclusive of BMSC dietary needs, food choices were still limited in the options and amount available. School and catering staff stated that cost implications contributed to their menu development process. Despite this, there was an evident willingness to learn about the cultural food options and how these can be implemented in future school menus. Suggestions discussed included an increase in the use of halal meat in order to provide a more inclusive school food experience for BMSC.